Climate change, household vulnerability and smart agriculture: The case of two South African provinces - Mkhululi Ncube; Nomonde Madubula; Hlami Ngwenya; Nkulumo Zinyengere; Leocadia Zhou; Joseph Francis; Talentus Mthunzi; Crespo Olivier; Tshilidzi Madzivhandila (Jàmbá, 2016)
The impact of climate-change disasters poses significant challenges for South Africa, especially for vulnerable rural households. In South Africa, the impact of climate change at the local level, especially in rural areas, is not well known. Rural households are generally poor and lack resources to adapt to and mitigate the impact of climate change, but the extent of their vulnerability is largely not understood. This study looked at the micro-level impact of climate change, evaluated household vulnerability and assessed alternative adaptation strategies in rural areas. The results indicate that climate change will hit crop yields hard and that households with less capital are most vulnerable. These households consist of the elderly and households headed by females. Households that receive remittances or extension services or participate in formal savings schemes in villages are less vulnerable. The results suggest that households need to move towards climate-smart agriculture, which combines adaptation, mitigation and productivity growth.